POTENSI AKTIVITAS ANTIBAKTERI EKSTRAK DIKLOROMETANA DAN METANOL BUNGA TEROMPET EMAS (Allamanda cathartica L.) TERHADAP BAKTERI Staphylococcus aureus ATCC 25923 - Ayu, Linda; Kuspradini, Harlinda; Ruga, Ritbey (Jurusan Kimia FMIPA UNMUL, 2024)
Potential antibacterial activity of dichloromethane and methanol extracts of the golden trumpet flower (A.cathartica L.) against S. aureus ATCC 25923 has been conducted. This study aimed to determine the values of thedichloromethane and methanol extracts of A. cathartica L. The antibacterial activity test was conducted using agardiffusion method and carried out in triplicate. The obtained results from the dichloromethane extract and methanol extractof the golden trumpet flower (A. cathartica L.) showed antibacterial activity with inhibition zone diameters of 9.66 mmfor dichloromethane extracts and 8.66 mm for methanol extracts against S. aureus ATCC 25923 bacteria.